Pengembangan Media Pembelajaran Kosakata Berbasis Audio-visual untuk Peningkatan Kompetensi Berbahasa Indonesia Anak Usia Dini - Masnur Muslich; - Suyono (Sekolah Dasar : Kajian Teori dan Praktik Pendidikan, 2009)
Abstract: Learning media plays an important role to assist early learners in learning Indonesian The current study aims at developing media for learning vocabulary to improve early learners’ competence in learning Indonesian. An R@D design was employed for the purpose. It is expected that the media as the product of this study can be of use by teachers in early learner education institutions.